Transformasi Pendidikan Digital dan Reproduksi Ketimpangan Sosial: Studi Empiris di Indonesia - Yaqin, Lalu Nurul; Nugraha, Rizky Aditya; Fadhilah, Nur Aini (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The digital transformation of education in Indonesia has accelerated alongside national policies promoting educational digitalization and technology integration. However, this transformation has not consistently led to equitable educational outcomes and, in many cases, has reproduced existing social inequalities. This study aims to analyze how digital education transformation contributes to the reproduction of social inequality in Indonesia, particularly across regional, socioeconomic, and institutional dimensions. Employing a qualitative descriptive approach, this research utilizes a systematic literature review and thematic analysis of 27 national and international scholarly articles. The findings reveal that disparities in technological access, digital literacy, infrastructure, and institutional capacity are key factors exacerbating educational inequality. Furthermore, uniform and context-insensitive digital education policies tend to marginalize vulnerable groups, especially those in rural and underdeveloped regions. This study concludes that Indonesia’s digital education transformation requires inclusive, context-sensitive, and adaptive policy frameworks to ensure that digitalization functions as a tool for educational equity rather than a mechanism for social reproduction of inequality.